Description of two previously unknown anuran vocalizations from the Caribbean rainforests of Costa Rica: Descripción de dos vocalizaciones de anuros previamente desconocidas del bosque húmedo caribeño de Costa Rica - Salazar, Stanley; Montes-Correa, Andrés Camilo; Barrio-Amorós, César L. (Anartia, 2021)
The small Central American country of Costa Rica is known to have one of the highest diversities of amphibians per surface area on the planet, with 215 species in 51.100 km2 (Savage 2002, Leenders 2016). Despite being one of the best-studied countries in Latin America for its amphibians fauna, with a long tradition of foreign and national herpetologists regularly publishing about them (summa-rized in Savage 2002, Leenders 2016), many aspects regarding the taxonomy and natural history of most amphibians remain poorly understood or completely unknown.